Finding Global Minima with a Filled Function Approach for Non-Smooth Global Optimization - Weixiang Wang; Youlin Shang; Ying Zhang (Discrete Dynamics in Nature and Society)
A filled function approach is proposed for solving a non-smooth unconstrained global optimization problem. First, the definition of filled function in Zhang (2009) for smooth global optimization is extended to non-smooth case and a new one is put forwarded. Then, a novel filled function is proposed for non-smooth the global optimization and a corresponding non-smooth algorithm based on the filled function is designed. At last, a numerical test is made. The computational results demonstrate that the proposed approach is effcient and reliable.